2010
DOI: 10.2118/114130-pa
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Mud Losses in Naturally Fractured Reservoirs: The Effect of Rheology

Abstract: Summary Significant fluid loss while drilling through fractured formations is a major problem for drilling operations. From field experience, we know that the type and rheological parameters of the drilling fluid have a strong impact upon the rate and volume of losses. A mathematical model for Herschel-Bulkley [yield-power-law (YPL)] drilling-fluid losses in naturally fractured formations is presented. As a result, the effect of rheological properties of drilling fluid such as yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 7 publications
2
27
1
Order By: Relevance
“…Recognizing the essential role of the fluid rheology, Majidi et al 6 developed a theoretical model for a more realistic and frequently used rheological behavior of drilling fluids; i.e., Yield-Power-Law (YPL) fluids 7 . The mathematical model for Yield-Power-Law fluids was derived using a similar approach involved with Lietard's model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recognizing the essential role of the fluid rheology, Majidi et al 6 developed a theoretical model for a more realistic and frequently used rheological behavior of drilling fluids; i.e., Yield-Power-Law (YPL) fluids 7 . The mathematical model for Yield-Power-Law fluids was derived using a similar approach involved with Lietard's model.…”
Section: Introductionmentioning
confidence: 99%
“…However, in this model 6 , the formation fluid was not accounted for since it was assumed that the whole overbalance pressure was applied only across drilling fluid bank and no pressure profile was considered beyond the front of the invading mud in the fracture. This means that no resistance was considered against invading mud due to the infinite compressibility or low viscosity of formation fluids.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, Eq. 5 can be simplified using the formulation proposed by Majidi et al 2010.As an example, the data shown in Table 1 is used to calculate the fluid loss volume. The volume of loss for a fracture with 500 microns width is shown in Fig.…”
Section: Losses Through Small Natural Fracturesmentioning
confidence: 99%
“…They believed that the mud losses would eventually stop because of the yield stress of drilling fluid. Majidi et al presented a mathematical model for Herschel‐Bulkley drilling‐fluid losses in naturally fractured formations, the effect of mud rheological properties was investigated, and it was found that yield stress can control the ultimate volume of losses, and the shear‐thinning effect can greatly decrease the rate of losses.…”
Section: Introductionmentioning
confidence: 99%